2021
DOI: 10.1007/s42729-021-00675-x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Oxalic Acid Protects Germinating Chickpea Seeds Against Cadmium Injury

Abstract: The objective of the present study was to elucidate the mechanism by which oxalic acid (OA) alleviates cadmium (Cd) stress. Chickpea (Cicer arietinum L.) seeds were treated with 200 µM CdCl 2 for 6 days or 3 days followed by the combination 200 µM Cd + 100 µM OA for three additional days. Exogenous OA mitigated the growth inhibition by Cd of both roots and shoots. This positive effect can be attributed to the increased OA exudation from roots and the alleviation of the Cdinduced depletion of endogenous OA in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…These statistical tools also revealed that the main cause behind the various consequences of DBP accumulation and translocation. The similar observations were found in the study of Sakouhi et al (2021) .…”
Section: Discussionsupporting
confidence: 91%
“…These statistical tools also revealed that the main cause behind the various consequences of DBP accumulation and translocation. The similar observations were found in the study of Sakouhi et al (2021) .…”
Section: Discussionsupporting
confidence: 91%
“…Cr toxicity damages plasma membrane functionality and induces a rapid change in the lipid composition of the cell membrane 12 . Changes in plasma membrane integrity also influence the H + -ATPase activity, which has been found to decrease under heavy metal stress in maize 20 , chickpea 21 , 22 , cucumber 23 , and rice 24 . Thus, plant characteristics that are susceptible to Cr toxicity may also be associated with plant tolerance to heavy metal contamination.…”
Section: Introductionmentioning
confidence: 99%
“…High excretion of oxalate from the root of Sedum alfredii Hance potentially enhanced Cd uptake and accumulation [18]. Other negatively charged anions, such as citric, malic and acetic acid, have also been shown to be incapable of forming stable Cd complexes, which influences plant Cd uptake [19]. Under iron (Fe) deficiency, Cd stress caused greater phytosiderophores production by maize roots, but this release failed to protect maize plants from Cd toxicity [20,21].…”
Section: In Rhizospherementioning
confidence: 99%